Cellular localization of androgen synthesis in equine granulosa-theca cell tumors: Immunohistochemical expression of 17α-hydroxylase/17,20-lyase cytochrome P450 - Assis Neto, A. C A [UNESP]; Ball, B. A.; Browne, P.; Conley, A. J. (Elsevier, 2010)
Elevated blood testosterone concentrations, often accompanied by male-typical behaviors, is a common signalment of mares with granulosa-theca cell tumors (GCTCs), but no definitive information exists regarding the cellular differentiation of tumors associated with androgen secretion. This study was conducted to localize and thereby define the cellular expression of 17α-hydroxylase/17,20-lyase cytochrome P450 (P450c17), the enzyme most directly responsible for androgen synthesis, in 30 GTCTs and control tissues (gonads and adrenal glands) using immuno-histochemistry (IHC). Immuno-reactivity for P450c17 was evident in approximately half of 30 specimens examined, was most consistent in the interstitial cells surrounding existing or developing cysts, and was less intense in cells within cysts in the smaller proportion of specimens where this was observed. In control tissues, the expression of P450c17 was localized primarily in theca interna of normal ovarian follicles, in theca-lutein cells of some corpora lutea, but not in granulosa-lutein cells. Testicular interstitial cells and islands of adreno-cortical cells located in the adrenal medulla of the adrenal cortex further established the specificity of the antisera used. These data provided the first substantive evidence that polyhedral cells identified previously in GTCTs by histopathology have the potential to synthesize and secrete androgens, similar to theca interna and theca lutein cells in normal equine ovaries. © 2010 Elsevier Inc.
Keywords: Androgen; Differentiation; Horse; Ovary; Steroidogenesis; androgen; steroid 17alpha monooxygenase; animal; animal disease; biosynthesis; enzymology; female; granulosa cell tumor; horse; horse disease; immunohistochemistry; male; metabolism; ovary tumor; thecoma; Androgens; Animals; Female; Granulosa Cell Tumor; Horse Diseases; Horses; Immunohistochemistry; Male; Ovarian Neoplasms; Steroid 17-alpha-Hydroxylase; Thecoma; Equidae